Fiqh Mu’āmalah in Theory and Practice: An Overview of Islamic Economics - M Qoshid Al Hadi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2022)
The Islamic economic paradigm and worldview have resulted in competitive Islamic finance industry in global finance. In the face of intense competition in the global financial industry, Islamic finance requires innovative contracts or products based on sharia through fiqh mu’āmalah. This article aims to understand the issue of fiqh mu’āmalah in Islamic economics. Using descriptive analysis, the author describes the relationship between fiqh mu’āmalah and sharia finance and the prohibition of mu’āmalah, hybrid-contract, Maqāshid sharia, and its supervision. The conclusion in this article clarifies the concept of the prohibition of fiqh mu’āmalah to its supervision without hindering the innovation of Islamic financial activities.Paradigma ekonomi Islam dan cara pandangnya (worldview) telah menghasilkan industri keuangan syariah yang kompetitif dalam keuangan global. Dalam menghadapi persaingan sengit industri keuangan global maka keuangan syariah membutuhkan akad atau produk yang inovatif berbasis syariah melalui fiqih mu’āmalah. Artikel ini bertujuan untuk memahami isu fiqih mu’āmalah dalam studi ekonomi Islam. Dengan menggunakan analisis deskriptif, penulis mendeskripsikan hubungan fiqih mu’āmalah dan keaungan syariah serta larangan mu’āmalah, multi akad, Maqāshid syariah dan pengawasannya. Kesimpulan dalam artikel ini menjernihkan konsep tentang larangan fiqih mu’āmalah hingga pengawasannya tanpa menghambat inovasi dari aktivitas keuangan syariah.